Design and development of injectable intraperitoneal sustained release drug delivery system for ovarian cancer - Nazir, Chaudhry Zahid (2020)
Multiple clinical trials have shown improved survival after IP (intraperitoneal) over IV (intravenous) chemotherapy in women with optimally resected ovarian cancer and the National Cancer Institute (NCI) encourages the use of IP chemotherapy. Despite this, IP chemotherapy has still not been widely accepted due to various concerns.